Dermatoglyphics and Their Association with Gender and Blood Group in Medical Students at Islam Medical and Dental College: Dermatoglyphics Association with Gender and Blood Group in Medical Students - Zeeshan, Rana Muhammad; Ahmad, Riaz; Junaid, Muhammad; Ahmad, Aftab; Rasheed, Aaqiba; Zafar, Maria (Pakistan Journal of Health Sciences, 2024)
Dermatoglyphics is defined as the study of the patterns present on fingers, toes, palms and soles which develop by the 24th week of gestation and remain permanent throughout life. A significant association has been confirmed between the different ABO blood groups, gender and dermatoglyphic patterns. Objectives: To investigate the fingerprint patterns among male and female students at Islam Medical and Dental College, Sialkot, and their relationship with blood groups. Methods: This cross-sectional study was conducted at Islam Medical and Dental College, Sialkot, in the year 2023 from mid-November to mid-December. 300 healthy students, aged 20 to 22 years, including 108 male and 192 female, participated. Fingerprints were collected using an ink pad, while blood grouping was performed using the slide method. Using SPSS version 26.0, the data were analyzed. The chi-square test (p<0.05) was used to evaluate relationships, and continuous variables were given as mean ± SD and categorical variables as frequencies. Results: The most prevalent blood type among all students was O+, and the most common fingerprint pattern was the loop pattern. Blood group and fingerprint pattern were shown to be significantly correlated in female medical students; those with loop patterns indicated a higher frequency of the B+ blood group, while those with whorl patterns indicated a higher frequency of the O+ blood type. Conclusions: It was concluded that a significant association of blood groups with dermatoglyphic patterns in female medical students was seen whereas in male, there was no link between blood groups and fingerprint patterns